The Transition of Care From Pediatric to Adult Health-Care Services of Vertically HIV-Infected Adolescents: A Pilot Study - Continisio, Grazia Isabella; Lo Vecchio, Andrea; Basile, Francesca Wanda; Russo, Carla; Cotugno, Maria Rosaria; Palmiero, Giulia; Storace, Cinzia; Mango, Carmela; Guarino, Alfredo; Bruzzese, Eugenia (Frontiers in Pediatrics, 2020)
Objective: Clinical and psychological HIV-related problems peak during adolescences, which coincides with the transition of adolescent with vertically HIV infection (acquired by the mother during the pregnancy or at time of birth), from pediatric centers to infectious disease specialists. To promote transition, a combined medical-psychological intervention was developed and the impact on viro-immunological status and psychological functioning condition was measured. Methods: Thirteen vertically-infected patients aged 13-20 years were followed for 24 months by pediatricians, infectious disease specialists, a psychologist, and a nurse. The intervention period was of 12 months. Clinical and psychological evaluations were performed at 0 (T0) and12 months (T12) and 6 months after transition to an adult center (T18). Psychological outcomes were assessed using standardized questionnaires for quality of life and self-esteem. Results: In 11/13 participants, the number of pills and administrations per day were significantly reduced. Patients with undetectable viral load and CD4+ >25% increased from 61% to 69% and from 61% to 92% respectively. Six months after transition, all patients exhibited an undetectable viral load. Adolescents’ awareness of the severity of the disease and the risk of sexual transmission were generally poor. Patients classified with “severe” psychological distress according to the quality of life index decreased from 34% to 15%. Similar results were observed 6 months after the transition to adult care. No difference was observed in the self-esteem index after intervention. Conclusions: Transition provides opportunities to improve immunological and psychological outcomes in HIV infection. Specific protocols should be developed to optimize resilience and psychological well being, including routine psychological support for all patients and information on transmission of HIV through sexual contacts.